The "Shortage" of Engineers - Hansen, W. Lee (The Review of Economics and Statistics, 1961)
W HETHER or not shortages of highly educated and trained personnel, such as engineers and scientists, existed or were serious in recent years has been the subject of widespread discussion and indeed controversy.1 Typically, this discussion focuses on the question of whether there ought to be more engineers and scientists, in terms of our competition with the Russians, for example. It is not surprising then that controversy flourishes, since the answer to this question depends ultimately on one's value judgments, with respect to market and nonmarket variables. But more fundamentally, much of the disagreement over the issue stems from the variety of meanings attached to the term and the lack of empirical tests. To clarify the matter, Blank and Stigler in their recent book2 define and provide an empirical test for the existence of shortage. This paper re-examines some of the empirical evidence they submit and supplements it with additional evidence, part of which extends the analysis to more recent date. Briefly, here is summary of the BlankStigler approach and findings.3 They begin with this definition of shortage: a shortage exists when the number of workers available (the supply) increases less rapidly than the number demanded at the salaries paid in the recent past. Then salaries will rise, and activities which once were performed by (say) engineers must now be performed by class of workers who are less well trained and less expensive.4 (Italics in original.) Since I929, and more particularly since I939, they find that the earnings position of engineers has deteriorated substantially relative to all earners and to other professional earners. Although they note slight upturn in the relative earnings position of engineers since the beginning of the Korean WVar, this reversal is characterized as a minor cross-current in tide. Thus, the evidence leads them to conclude that there has been no but rather an increasingly ample supply of engineers. Furthermore, they predict that the downward trend in relative earnings position will continue.5